Best Answer

Watch closely:

6x = 3x + 27

Subtract 3x from each side:

3x = 27

Divide each side by 3:

x = 9

Q: How do you solve 6x equals 3x plus 27?

Write your answer...

Submit

Still have questions?

Continue Learning about Other Math

3x + 2y = 12 ie 2y = 12 - 3x so y = 6 - 3x/2

y-3x+6y=12 7y=3x+12 y=3x/7 +12/7

You cannot solve one linear equation in two unknown variables.

3x - 2 = 2x + 4 3x - 2x = 4 + 2 x = 6

7x+6 = -3x-24 7x+3x = -24-6 10x = -30 x = -3

Related questions

4+3x-27=-12 To solve it... 3x= -12-4+27 3x= 11 x= 11/3 x= 3.666

3

x = -8

23

x=7

x2 plus 3x plus 3 is equals to 0 can be solved by getting the roots.

You do not have enough information to solve this problem. More accurately, you do not have enough information to assign a numeric value to z. However, abstractly, you could say that z=27-3x-4y.

-3x + 5 = 20 -3x = 15 x = -5

3x + 2y = 12 ie 2y = 12 - 3x so y = 6 - 3x/2

x = 6

x = -8

7x = 3x - 12 4x=-12 x=-3